Pendampingan Pembuatan Laporan Cash Flow dalam Mengelola Keuangan Rumah Tangga di Jalan Siwalan Manyar Gresik - Anisaul Hasanah; Dini Ayu Pramitasari; Bustanul Ulum (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The purpose of this service is to provide knowledge to residents on Jalan Siwalan Manyar regarding making cash flow reports (Cash Flow) in managing household finances, especially for residents of Siwalan Manyar so that expenses are not greater than their expenses. To realize this goal, we are holding a training program entitled